Perspectives on constitutional responsibility some countries in the world introduction and comparison with Vietnam - Thi Hai Van, Nguyen; Ninh, Chu Van (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2023)
The Constitution is the document with the highest position in the legal hierarchy, acting as the original law, as a basis for other documents in the system of legal documents of each country. The contents are indispensable in most constitutions. With the highest legal position and effect, the constitution plays an important role in ensuring human rights and citizens' rights by recognizing these rights, binding the state's responsibility in realizing these rights. constitutional rights and the constitution is also a document restricting the power of the state. Constitutional liability is an important tool for strengthening and developing democracy, but in practice, not all countries are directly mandated by their constitutions or legal documents constitution as a special form of liability. This article gives a general review of constitutional liability in a few diffe ent nations to compare and offer ideas for considering the constitutional liability institution in Vietnam.